If we are given that x + x 1 = a , then we know that x 2 + x 2 1 = a 2 − 2 and x 3 + x 3 1 = a 3 − 3 a . However, it's not too clear how we can relate the latter 2 equations with each other.
Let x be a real number such that x 3 + x 3 1 = 1 0 2 , what is the value of x 2 + x 2 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A more intuitive solution would have been better
First, we let x 2 + x 2 1 = a , We see from the properties Calvin listed that x + x 1 = a + 2 , so x 3 + x 3 1 = a + 2 ⋅ ( a − 1 ) = a 3 − 3 a + 2 .
Since x 3 + x 3 1 = 1 0 2 , we have a 3 − 3 a + 2 = 1 0 2 = 2 0 0 , so a 3 − 3 a + 2 = 2 0 0
Using, RRT, we find that a = 6 is a solution. Using synthetic division, we find that the resulting quadratic, a 2 + 6 a + 3 3 , has no real solutions. Thus a = 6 is the solution we are looking for.
What is RRT??
I'll admit that I did this "by eye": 1 0 2 = 2 2 ⋅ 5 = a 3 − 3 a = a ⋅ ( a 2 − 3 ) . Noting that 8 = 2 2 and 8 − 5 = 3 , it becomes clear that a 2 = 8 . So a 2 − 2 = 6 = x 2 + x 2 1 .
I did check first, using the factorization of a "sum of two cubes", that the stated relation between x + x 1 , x 2 + x 2 1 , and x 3 + x 3 1 is true in general. But it was when I was faced with the possibility of having to solve the cubic equation that the factorization of 1 0 2 occurred to me. So I don't know that I'd recommend this as a general method.
I Did the same way as well...
Suppose x < 0 , then the equation x 3 + x 3 1 = 1 0 2 can't be fulfilled, thus x > 0 which makes a positive real.
We have a 3 − 3 a = 1 0 2 , and we want to evaluate a 2 − 2 , let b = a 2 , so b is real too.
b b − 3 b b ( b − 3 ) b ( b − 3 ) 2 = = = 1 0 2 1 0 2 2 0 0
With 2 0 0 = 5 2 × 8 , then b = 8 ⇒ a 2 − 2 = b − 2 = 6
Alternatively, because the cubic equation is depressed, this motivates me to solve it trigonometrically. Let a = 2 cos θ for complex number θ . And we want to evaluate a 2 − 2 = 2 cos ( 2 θ ) . By double and triple angle formula,
( 2 cos θ ) 3 − 3 ( 2 cos θ ) 2 ( 4 cos 3 θ − 3 cos θ ) cos ( 3 θ ) = = = 1 0 2 1 0 2 5 2
Then, c o s ( 6 θ ) = 2 cos 2 ( 3 θ ) − 1 = 9 9 , or 4 cos 3 ( 2 θ ) − 3 cos ( 2 θ ) = 9 9 , by Rational Root Theorem, cos ( 2 θ ) = 3 is a root, thus a 2 − 2 = 2 × 3 = 6
Problem Loading...
Note Loading...
Set Loading...
Since x 3 + x 3 1 = 1 0 2 hence x 6 + x 6 1 = ( 1 0 2 ) 2 − 2 = 1 9 8 .
Let x 2 + x 2 1 = a , then we have a 3 − 3 a = 1 9 8 . This gives us ( a − 6 ) ( a 2 + 6 a + 3 3 ) = 0 . We have a real root a = 6 , and 2 complex roots.